The Impact of Children on Intimate Partner Abuse Victims' Service-Seeking. Issue 3 (27th May 2017) - Stephens, Emily; Melton, Heather C.
Abstract : Intimate partner abuse is a major problem. This is especially true when there are children present. In attempt to stop the cycle of abuse, it is of critical importance to understand the impact children have on the relationships and the decision-making process of those involved. This research is part of a larger project examining the help-seeking behaviors of victims of intimate partner abuse. Face-to-face interviews were conducted with 26 victims of intimate partner abuse who eventually sought services. This paper reports on how children affect the decision of their parent to either seek services while in an abusive situation or to postpone seeking services. This study focuses on 19 of those respondents with children. Both quantitative and qualitative data analyses were conducted. This paper utilizes part of the qualitative data relating to the import of children in the decision-making process. Analysis reveals that for all respondents, children were important to their decision-making process. Several themes related to children were identified, including those who identified leaving the situation and seeking services because of their children and those who postponed seeking services because of their children. Implications for prevention and intervention in cases of intimate partner abuse will be discussed.